2016
DOI: 10.1016/j.freeradbiomed.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The chemical biology of protein hydropersulfides: Studies of a possible protective function of biological hydropersulfide generation

Abstract: The recent discovery of significant hydropersulfide (RSSH) levels in mammalian tissues, fluids and cells has led to numerous questions regarding their possible physiological function. Cysteine hydropersulfides have been found in free cysteine, small molecule peptides as well as in proteins. Based on their chemical properties and likely cellular conditions associated with their biosynthesis, it has been proposed that they can serve a protective function. That is, hydropersulfide formation on critical thiols may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 51 publications
5
83
0
Order By: Relevance
“…The in situ generation of hydropersulfides can be accomplished using a penicillamine-based donor species MCPD giving the hydropersulfide MCP-SSH [22,23,35] (Figure 1a). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The in situ generation of hydropersulfides can be accomplished using a penicillamine-based donor species MCPD giving the hydropersulfide MCP-SSH [22,23,35] (Figure 1a). …”
Section: Resultsmentioning
confidence: 99%
“…The results presented herein indicate an accessible RSSH/RSS· (or RSS − /RSS·) redox couple with both redox partners being fairly stable to, for example, reaction with O 2 or NO. Although purely speculative at this time, it is intriguing to consider that cellular oxidative stress, conditions likely conducive to hydropersulfide formation [22], can generate persulfides in proteins, allowing them to then participate in a redox or electron transfer process. That is, a protein thiol may not possess the proper redox properties to participate in an electron transfer or redox event, but conversion to the corresponding persulfide may act as a “redox gate” allowing such chemistry to occur (Figure 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it may be expected that the reaction of HNO with a persulfide is significantly faster than with the corresponding thiol. Indeed, it was found that HNO was capable of reacting with a hydropersulfide [24], although the chemical details of this interaction await clarification. Interestingly, when compared to the corresponding thiol, the HNO-modified persulfide was more easily reduced back to the thiol by an exogenous reductant (dithiothreitol, DTT).…”
Section: Hno Chemistrymentioning
confidence: 99%
“…The rush of discovery for H 2 S and its derivative compounds started in the late 1980s by reports of potential biological roles of H 2 S in modulatory and signalling pathways 4. The associated probable health benefits generated a renewed interest in the study of H 2 S, as reflected in the exponential increase in the number of publications 4…”
mentioning
confidence: 99%